Urgensi Pembelajaran Agama-agama di Sekolah Menengah Tingkat Atas - Hamid Nasuhi (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2021)
Symptoms of conservatism, exclusivism, and extremism in religious expression in Indonesia seem to have strengthened since the Reformation era. These symptoms come to the surface through the acts of intolerance towards different people and groups, both within the religion itself and with other religions. In fact, not infrequently these acts are in the form of extreme violence which is included in the category of terrorism. The state has actually tried to overcome the impact of these worrying phenomena, but the results are still not optimal. This article tries to contribute the ideas to overcome this situation through education, especially religious education. In religious education, which is a compulsory subject in schools from basic to highest education, it is necessary to provide introduction to other religions, especially religions in Indonesia. This material introduction can be given to students in class XI or XII, assuming that they are mature enough to accept differences. In addition, in this internet era, religious education needs to be delivered in creative and innovative ways so that this subject is attractive to students.